Зміна функціональних параметрів мехатронних систем з планетарними гідромоторами за різних умов експлуатації - Панченко, Анатолій Іванович; Волошина, Анжела Анатоліївна; Ковязін, Олексій Сергійович; Панченко, Ігор Анатолійович; Волошин, Анатолій Анатолійович; Panchenko, Anatolii; Voloshina, Angela; Koviazin, Oleksii; Panchenko, Ihor; Voloshin, Anatolii (Запоріжжя : Видавничій дім "Гельветика", 2025)
UA: На сьогоднішній день актуальним завданням є створення самохідних машин спеціального призначення (дорожніх, будівельних, сільськогосподарських тощо) підвищеної мобільності. Для покращення функціональних параметрів мехатронних систем самохідних машин із гідравлічним приводом ходової частини проведені експериментальні дослідження мехатронної системи самохідної машини з гідравлічним приводом ходової частини з регульованим насосом та мехатронними модулями на базі планетарних гідромоторів та обґрунтуванні раціональні режими експлуатації регульованого насоса та планетарних гідромоторів, що покращують функціональні параметри мехатронної системи самохідної машини з гідравлічним приводом мехатронних модулів (мотор-коліс) на базі планетарних гідромоторів. /// EN: Today, the development of self-propelled special-purpose vehicles (road, construction, agricultural, etc.) with increased mobility is a pressing issue. To improve the functional parameters of mechatronic systems in self-propelled vehicles with hydraulic undercarriage drives, experimental studies were conducted on the mechatronic system of a self-propelled vehicle with a hydraulic undercarriage drive, featuring an adjustable pump and mechatronic modules based on planetary hydraulic motors. The study also substantiated rational operating modes for the adjustable mechatronic system of a self-propelled vehicle with a hydraulic drive and mechatronic modules (motor-wheels) based on planetary hydraulic motors. Experimental studies were conducted using a mechatronic system for a self-propelled vehicle with a hydraulic undercarriage drive, consisting of an adjustable pump and two mechatronic modules (motor-wheels) based on planetary hydraulic motors. The mechatronic system has a regulator that ensures the self-propelled vehicle’s engine operates in constant power mode. As the load in the mechatronic system’s hydraulic drive changed, determined by the pressure drop of the working fluid, the pump power was maintained by continuously adjusting the pump control parameter. Experimental studies have substantiated rational operating modes for pumps and hydraulic motors, improving the performance of the mechatronic system of a self-propelled vehicle with a hydraulic drive for mechatronic modules (wheel hub motors) based on planetary hydraulic motors. It has been established that the most efficient pump operating modes involve varying the pump control parameter within the range of 0.5 to 1.0 MPa, and a working fluid pressure differential of 7 to 21 MPa. High planetary hydraulic motor efficiency is ensured by operating them within a relative speed range of 0.25 to 1.0 MPa, with a working fluid pressure differential of 7 to 21 MPa.
Changing the functional parameters of mechatronic systems with planetary hydraulic motors under various operating conditions
Keywords: мехатронна система; гідравлічний привід; мехатронний модуль; планетарний гідромотор; регульований аксіально-поршневий насос; функціональні параметри; mechatronic system; hydraulic drive; mechatronic module; planetary hydraulic motor; adjustable axial piston pump; functional parameters